SLIP OF TONGUE PRODUCE BY DEBATERS IN "INTELLIGENCE-HIGH SCHOOL DEBATE" EPISODE 5 - Adinda Maulida (ReALL - Research on Applied Linguistics and Literature, 2023)
Anyone who is communicating with another person may unintentionally make a slip of the tongue, even in an academic environment like a debating tournament. There are many factors that cause slip of the tongue during delivering an argument, especially in psychological variables, including feeling under pressure or anxious. This study aims to analyze debaters' slip of the tongue from episode 5 of the television show "IntelligenceHigh School Debate." Identifying the types of slip of tongue using the theories of Haley (2001) and Fromkin (1973). This study also aims to determine the frequency of type slip of tongue in the video debate tournament. This current study uses qualitative descriptive, and documentary techniques also video recording documents as a tool in order to collect that data. The final result showed that the debaters from the competition engaged in haplologies, phoneme anticipation, phoneme preservation, phoneme deletion, affix deletion, word blending, word exchange, morpheme exchange, word substitution, and phrase blending. 36 data of information relating to slips of the tongue were discovered. 14 data points for word substitution, 5 for word blends, 4 for phoneme deletion, 3 for affix deletion and misderivation, 2 for morpheme exchange and haplologies, and 1 for word exchange, phrase blends, and phoneme anticipation. During the debate segment, word substitution was frequently used by the debaters.